2016
DOI: 10.3390/ma9070524
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Supercritical Fluid Extraction of Total Alkaloids, Peimisine, Peimine and Peiminine from the Bulb of Fritillaria thunbergii Miq, and Evaluation of Antioxidant Activities of the Extracts

Abstract: Supercritical fluid extraction (SFE) was used to extract total alkaloids, peimisine, peimine and peiminine from the bulb of Fritillaria thunbergii Miq. The antioxidant capacity of the extracts was evaluated by DPPH radical scavenging activity (DPPH-RSA), ABTS radical scavenging activity (ABTS-RSA) and ferric reducing capacity (FRAP) assay. A central composite design (CCD) with four variables and five levels was employed for optimization of process parameters, and response surface plots were constructed in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Pathological and biological studies have confirmed that the active principle compounds of Fritillaria thunbergii are alkaloids, including peimisine, peimine and peiminine [7,8]. In recent studies, peiminine has been reported to have anti-inflammatory, analgesic, and antitussive effects and to be able to ameliorate acute lung injury [9][10][11][12].…”
Section: Introductionmentioning
confidence: 86%
“…Pathological and biological studies have confirmed that the active principle compounds of Fritillaria thunbergii are alkaloids, including peimisine, peimine and peiminine [7,8]. In recent studies, peiminine has been reported to have anti-inflammatory, analgesic, and antitussive effects and to be able to ameliorate acute lung injury [9][10][11][12].…”
Section: Introductionmentioning
confidence: 86%
“…However, the extraction and purification of SMs from wild natural plants normally require a complex and time consuming process, and even so, the yield of the desirable end-product is often very low [ 20 , 21 , 22 , 23 ]. Consequently, finding practical approaches to intensify the process and enhance the yield pose a serious challenge to researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that mangiferin can inhibit mastitis induced by LPS via suppressing NF-κB and NLRP3 signaling pathways, and resveratrol inhibits LPS-induced mice mastitis through attenuating the Mitogen-activated protein kinase (MAPK) and NF-κB signaling pathway [ 6 , 7 ]. Peiminine is a natural product of alkaloids, which comes from Fritillaria [ 8 ]. Peiminine ( Figure 1 ) is a monomer derived from a traditional Chinese medicinal herb.…”
Section: Introductionmentioning
confidence: 99%